2022
DOI: 10.1136/ijgc-2022-003387
|View full text |Cite
|
Sign up to set email alerts
|

Quality is more important than quantity: pre-operative sarcopenia is associated with poor survival in advanced ovarian cancer

Abstract: BackgroundSarcopenia is prevalent among older patients with cancer and is associated with poor outcomes.ObjectiveTo explore the relationship between muscle mass, quality, and patient age with overall survival after surgery for advanced ovarian cancer.MethodsPatients with advanced stage (IIIC/IV) ovarian cancer who underwent primary cytoreductive surgery between January 2006 and July 2016 were included. Body composition measures were calculated from pre-operative CT imaging: skeletal muscle index (skeletal musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 32 publications
2
13
0
Order By: Relevance
“…We agree that advanced ovarian cancer represents an excellent model for evaluating the mechanisms of sarcopenia because of the catabolic state created by the disease. Sarcopenia is associated with increased age and with poorer outcomes in patients with advanced cancer, as reinforced by our study2 and others. Maccio and Madeddu3 highlight the need to investigate the interplay of patient fixed factors (age and stage), tumor biology, and energetics.…”
supporting
confidence: 86%
“…We agree that advanced ovarian cancer represents an excellent model for evaluating the mechanisms of sarcopenia because of the catabolic state created by the disease. Sarcopenia is associated with increased age and with poorer outcomes in patients with advanced cancer, as reinforced by our study2 and others. Maccio and Madeddu3 highlight the need to investigate the interplay of patient fixed factors (age and stage), tumor biology, and energetics.…”
supporting
confidence: 86%
“…However, skeletal muscle loss occurs during treatment and compromises the survival outcomes. [2][3][4][5][6][7] Muscle loss can be overlooked and may not be identified by changes in body weight. 5 Therefore, muscles in these patients should be assessed to identify loss and target interventions to preserve and recover muscle.…”
Section: Introductionmentioning
confidence: 99%
“…8 Previous studies have revealed the usefulness of CT-based muscle measurements in patients with ovarian cancer. [3][4][5][6] However, the utility of such measurements may be limited in clinical practice because the required process is labour-intensive and time-consuming. 9 To assess changes in muscle, pre-and post-treatment CT scans should be processed by specific software, and the muscle is manually or semi-automatically segmented on a cross-sectional image at L3 to calculate the area of skeletal muscle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We read with interest the study by Polen-De and colleagues 1 regarding the relationship of muscle quantity and quality with prognosis in patients with advanced ovarian cancer. They concluded that sarcopenia was associated with poorer survival, particularly among patients aged >60 years.…”
mentioning
confidence: 99%